Damaged starch in the flour mill: how to reduce the electricity bill - Dhotel, Charles Loubersac. (Kansas State University, 2012)
The purpose of the research reported in the thesis, here, is to quantify new value added possible in flour milling with the use of the SDmatic monitor, produced and sold by Chopin Technologies SAS. As an employee of Chopin, part of my responsibility is to market the SDmatic. The SDmatic was designed and is marketed to improve flour quality by providing automatic monitoring of starch damage in flour—damaged starch affects dough characteristics, which affects baking quality and the ideal damaged starch differs by type of bakery product. While the SDmatic is so marketed, Chopin, now, realizes that SDmatic might also benefit a flour miller by increasing operational efficiency of the mill, specifically by reducing the electrical energy used in milling. If that can be done, it would improve mill profitability, reduce energy demand and, thus, reduce the pressure on the climate and environment from energy production. To address that possibility, the thesis research studied the relationship between energy usage and damaged starch in the flour and, then, estimated the cost savings possible by using the SDmatic to mill flour to specifications most efficiently. Finally, those results were used to estimate the return on investment in the SDmatic from improved mill efficiency, alone. The research shows improvement in energy efficiency is definitely possible with better management and targeting of the level of starch damage in flour production. Such improved management is possible, today, because SDmatic dramatically reduces the difficulty and time required to measure damaged starch. Such monitoring has not been done in the past because of the cost and time involved with prior methods. SDmatic makes that possible and cost effective, now.
Keywords: Flour milling; SDmatic; Starch Damage; Mill Management Economics; Flour mill optimization; Economics, Commerce-Business (0505); Food Science (0359); Management (0454)